PERILAKU LENTUR KOMPOSIT BETON DAN ASPAL DENGAN KANDUNGAN BUTON GRANULAR ASPHALT (BGA) - Erwin Syaiful Wagola; Muhammad Tharik Kemal; Mentari Rasyid (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
This study aims to analyze the behavior of asphalt concrete composites with the addition of Granular Asphal Buton in the asphalt layer as a surface layer on the concrete. The method used in this study was an experimental method with three types of test specimens. Type I of subgrade, Type II of subgrade added to concrete slabs and Type III of subgrade plus concrete asphalt coated plates + BGA 8.5% The results showed Type I reached a peak load of 45.48 kN. Type II reaches a peak load of 142.44 kN. And type III The use of AC-WC + BGA 8.5% concrete layers as surface layers is able to withstand monotonic loads reaching 214.747 kN. The effect of the use of concrete and asphalt layers containing BGA on the subgrade increases the strength of the structure and reduces the stress that occurs in the soil.